The Role of E-Commerce Use, Capital Availability and Business Training on Performance of Small Medium Enterprise (SMEs) in Indonesia - Fahrina Mustafa; Tri Febrina Melinda; Tri Yusnanto; Arief Yanto Rukmana; Jamaluddin Majid (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2023)
This study aims to determine whether the simultaneous use of finance, business training, and e-commerce has a favorable and significant impact on microbusiness revenue. Multiple linear regression is being used in this quantitative research approach. The people who participate in microbusinesses and have received business training make up the population of this study. Purposive sampling, a non-probability sample technique, and a total of 100 respondents make up the approach employed in this study. The questions for this study were made available and directly completed by respondents using Google Forms. The Likert scale was employed by the author as a measurement in this study. The usage of e-commerce has a good and considerable impact on microbusiness income, according to the research findings. Microbusiness income is significantly and favorably impacted by capital. Microbusiness income is significantly and favorably affected by enterprise training. Microbusiness revenue benefits significantly and positively from the usage of e-commerce, financing, and business training all at once. 52% of microbusiness income is impacted by the usage of e-commerce, financing, and enterprise training. The other 48%, meanwhile, was affected by things unrelated to this study.